2004
DOI: 10.1590/s0100-879x2004001100003
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide release and cellular gluthatione peroxidase activity in leukocytes from children with persistent asthma

Abstract: Asthma is an inflammatory condition characterized by the involvement of several mediators, including reactive oxygen species. The aim of the present study was to investigate the superoxide release and cellular glutathione peroxidase (cGPx) activity in peripheral blood granulocytes and monocytes from children and adolescents with atopic asthma. Forty-four patients were selected and classified as having intermittent or persistent asthma (mild, moderate or severe). The spontaneous or phorbol myristate acetate (PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…Thus, oxidative stress is a relevant risk factor for lung damage in chronic inXammatory diseases (Marcal et al 2004). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, oxidative stress is a relevant risk factor for lung damage in chronic inXammatory diseases (Marcal et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…This inhibition can occur through the activation of endogenous antioxidants, as the glutathione peroxidase (GPX)/glutathione reductase system, which neutralizes the action of already formed free radicals. GPX reduces peroxidases and hydroperoxidases impacting on the cardiovascular system and respiratory tract, since oxidative stress can harm diVerent epithelia (like the nasal epithelium) when free radicals increase (Marcal et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils recruited by allergen challenge generate sustained ROS in the airways, which may promote allergic inflammation through ROS generation [26] . The effects of reactive oxygen species in asthma include decreased beta-adrenergic function in lungs, airway smooth muscle contraction, increased vascular permeability, bronchial hyperresponsiveness, increased mucus secretion, impaired ciliary activity, generation of chemotactic factors and lipid peroxidation, and secondary production of mediators with a bronchoconstrictor effect [27] . It has been demonstrated that neutrophils purified from bronchoalveolarlavage fluid and peripheral blood from patients with allergic asthma released significantly higher quantities of ROS compared to healthy individuals [13,19,[27][28][29] .…”
Section: Reviewmentioning
confidence: 99%
“…The effects of reactive oxygen species in asthma include decreased beta-adrenergic function in lungs, airway smooth muscle contraction, increased vascular permeability, bronchial hyperresponsiveness, increased mucus secretion, impaired ciliary activity, generation of chemotactic factors and lipid peroxidation, and secondary production of mediators with a bronchoconstrictor effect [27] . It has been demonstrated that neutrophils purified from bronchoalveolarlavage fluid and peripheral blood from patients with allergic asthma released significantly higher quantities of ROS compared to healthy individuals [13,19,[27][28][29] . In mice mode of asthma, the gp91phox deficiency mice, the dominant superoxide generating enzyme in neutrophils, had decreased ROS production, and attenuated allergic inflammatory response to allergen challenge [30] .…”
Section: Reviewmentioning
confidence: 99%
“…Oxidative stress, with decreased levels of superoxide dismutase, catalase and glutathione peroxidase, as indicators of exhausted antioxidant reserve capacity, often develops in sickly children, irrespective of the location of the inflammation process in the respiratory tract [20]. The increased lipid peroxidation against the background of antioxidant enzymes inhibition was detected in infants with severe pertussis, and bronchoobstructive diseases and can lead to some immune system disorders [21].…”
Section: Antibacterial Properties Of Neutrophilsmentioning
confidence: 99%